Proyecto de factibilidad para la implementación de una empresa productora y comercializadora de agua aromática refrescante a base de menta y manzanilla, en el Cantón Piñas, Provincia de El Oro - Valle Cueva, Karen Juliana (2017)
Marketing of bottled aromatic waters, is an opportunity that has not yet been exploited in Piñas Canton, none currently exist company dedicated to the production that can satisfy the need to quench the thirst with a healthy and medicinal DRINK, Different Relieves which also ailments and Improves Quality of Life Consumer. The product is very attractive to enter the market; f taking advantage of preference for the consumption of natural foods and the lack of similar beverages; : Why as a student of the School of Business Administration and enterprising future've seen Necessary develop "PROJECT FEASIBILITY FOR THE IMPLEMENTATION OF A COMPANY PRODUCER AND DISTRIBUTOR OF AROMATIC WATER REFRESHING BASED MINT AND MANZANILLA IN PIÑAS CANTON, EL ORO PROVINCE " a cause of the lack of industrial development in the Canton. This research was main objective of determining the feasibility of implementing a producer and marketer of a base aromatic water refreshing mint and chamomile in Piñas Canton province of El Oro, para commissioning Company , by which take into consideration the use of descriptive, inductive, deductive, analytical methods, and techniques such as observation, interview, Survey and sampling that allowed me to segment the population for the product sea Directed para Population Families Piñas Canton. For the full analysis of the project was required the study of market, technical study, administrative and legal study, financial study and finally the project evaluation. To determine product acceptance in the market, a survey was used to the buyers and sellers of Piñas Canton. Within the discussion the market study was established where demand was made; being able to obtain the unsatisfied demand is 230,131 liters for the first year, then the marketing plan, pricing, place and product advertising was established; In the technical study the location and size of the plant is detailed; In the administrative and legal study of the company's business group, the constitution, organization and functions manuals was determined. The financial study indicates the investment needed to implement the project, which is $ 34,354.92 dollars. Finally, the evaluation was carried out for which the following indicators were examined: Net Present Value of $ 47,672.33; Internal Rate of Return of 41.44%; Profit ratio Cost is 0.32 cents per dollar invested in the company; Period of Capital Recovery is 2 years, 6 months and 3 days; Sensitivity Analysis indicates that the project supports an increase in costs of 16.56% with a sensitivity of 0.99% and the sensitivity analysis in the decrease in revenues of 12.75% giving a sensitivity of 0.99% Concludes that the project is feasible, and the implementation of this project is recommended.